The effect of microbes and dissolved oxygen concentration on inorganic and organic substances elimination in a climate changing environment: The aerobic bioreactor - Mpho Muloiwa; Caliphs Zvinowanda; Innocentia Velaphi Sibiya (Environmental Challenges)
Microbes and dissolved oxygen (DO) concentration are the drivers in the wastewater treatment plant, aerobic bioreactor for the oxidation and decomposition of inorganic and organic substances. Due to global warming, surface and freshwater temperatures are increasing at an average of 1.08 °C. The rising climate temperatures suppress DO which threatens the availability of oxygen for respiration and survival of microbes, risking poor effluent being discharged into the environment. This study aimed to analyze the effect of microbes and DO concentration simultaneously on the elimination of inorganic and organic substances in a climate-changing environment. The results showed that biomass, COD (-0.578⁎⁎), and ammonia (-0.700⁎⁎) produced a negative relation while DO, ammonia (-0.214⁎⁎), and COD (-0.250⁎⁎) produced a negative relation. Although rising climate temperatures suppress DO, microbes strived under these conditions resulting in an effective aerobic bioreactor. Rising climate temperature (32.5 °C) produced the highest biomass (6.51 g/L), COD (145 mg/L), and ammonia (14.5 mg/L) elimination at the lowest DO (3.81 mg/L) concentration. Whereas normal operating temperature produced the lowest biomass (2.289 g/L), COD (94 mg/L), and ammonia (4.5 mg/L) elimination at the highest DO (4.83 mg/L) concentration. In addition, rising climate temperatures produced the highest COD (72.5 mg/L) and ammonia (7.25 mg/L) elimination rate compared with normal operating temperatures that produced the lowest COD (47 mg/L) and ammonia (2.25 mg/L) elimination rate. Therefore, the rising climate temperatures will not affect the microbes and DO concentration during the elimination of inorganic and organic substances, but rather enhance the performance of the aerobic bioreactor.